O processo de projeto sob a ótica da formação do Arquiteto e Urbanista da PUC GO - Silva, Polyana Rodrigues Franco da (2020)
The investigation about the design processes in the field of Architecture and Urbanism, in the context of teaching-learning of design practices, constitutes an important research area of the main Universities in Brazil. As these activities unfold in complex stages, it is necessary to bring new questions and reflections that allow possible readjustments and improvements in the teaching of creative activities. Thus, the dissertation has the objective of identifying the major influences capable of affecting processes in projects implemented on the course of Architecture and Urbanism at Pontifical Catholic University of Goiás (PUC-GO), an institution that has been responsible for training most of the State's professionals. For this, the used methodology started from the bibliographic / documentary research and studies of carried out production in the project disciplines. The results obtained reinforce the imbricated relationship between the institution's trajectory, the political pedagogical projects elaborated and the Project processes and project teaching that have been established over the years.